2021
DOI: 10.1016/j.imu.2020.100491
|View full text |Cite
|
Sign up to set email alerts
|

Investigating healthcare practitioners’ attitudes towards the COVID-19 outbreak in Saudi Arabia: A general qualitative framework for managing the pandemic

Abstract: Background Some previous studies have investigated the attitudes of healthcare professionals towards certain aspects of the COVID-19 outbreak. In addition, some general frameworks have been proposed to manage the pandemic. Objective The purpose of this article was to analyze the attitudes of healthcare practitioners in Saudi Arabia towards the treatment of patients with COVID-19, work planning of practitioners, leadership approaches to manage the pandemic, sharing infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…26 Taken together, increasing the accessibility to materials provided by health care authorities, intensive training programs for all categories of the healthcare workers, rigorous attentive protocols, and a commitment to change behavior/practice, will significantly benefit the spread of the outbreaks. 24,31,32,37,[40][41][42][43][44][45]47,48,60,78,84,131 Mushi et al suggested that "risk communication as an effective strategy to improve the attitude and practice of HCWs towards COVID-19 in Saudi Arabia". 89 Measures to enhance protection for HCPs and minimize psychological consequences/potential social stigmatization should be recognized in the planning stage before any pandemic.…”
Section: Participants Online Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…26 Taken together, increasing the accessibility to materials provided by health care authorities, intensive training programs for all categories of the healthcare workers, rigorous attentive protocols, and a commitment to change behavior/practice, will significantly benefit the spread of the outbreaks. 24,31,32,37,[40][41][42][43][44][45]47,48,60,78,84,131 Mushi et al suggested that "risk communication as an effective strategy to improve the attitude and practice of HCWs towards COVID-19 in Saudi Arabia". 89 Measures to enhance protection for HCPs and minimize psychological consequences/potential social stigmatization should be recognized in the planning stage before any pandemic.…”
Section: Participants Online Questionnairementioning
confidence: 99%
“… Baig/Dec 2020 39 Predictors of misconceptions, knowledge, attitudes, and practices of COVID-19 pandemic among a sample of Saudi population 2006 participants Online questionnaire The study participants had good knowledge, positive attitudes, and good practices, but several myths were also prevalent. Alanezi/ 2021 40 Investigating healthcare practitioners’ attitudes towards the COVID-19 outbreak in Saudi Arabia: A general qualitative framework for managing the pandemic 102/336 respondents Online questionnaire The parameters considered by the authors in their constructed qualitative framework for managing the COVID-19 pandemic in Saudi Arabia included “communication, effective leadership, coordination, and work planning, adequate treatment for patients, strict compliance with hospital rules/procedures, preventive/regulatory measures, and training/support for health professionals”. Shrivastava/ 2021 41 Assessment of knowledge and attitude of allied healthcare professionals about COVID-19 across Saudi Arabia 195 AHPs Online questionnaire - Allied healthcare professionals (AHPs) displayed a moderate level of knowledge and a good attitude towards COVID-19.…”
Section: The Searched Outcomesmentioning
confidence: 99%
“… 1 As of the middle of November 2020, there have been more than 53,700,000 confirmed cases of people infected and more than 1,300,000 reported deaths. 2 In Saudi Arabia, 539,698 infections and 8431 coronavirus-related deaths have been reported in the country since the pandemic began. In addition, Saudi Arabia has administered at least 32,281,173 COVID-19 vaccines, accounting for about 47% of the Saudi population.…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, effective leadership in the healthcare setting among healthcare workers, including nurses is highlighted in previous studies (Alanezi et al, 2021;Ratanjee & Foy, 2020), as one of the parameters or strategies to control the spread of COVID-19 infection. The utilization of transformational leadership is one of the strategies to battle the surge of the COVID-19 pandemic and has been reported in Liu et al (2021), as infections continue to increase despite the worldwide administration of the COVID-19 vaccine.…”
Section: Introductionmentioning
confidence: 99%